Applying software product line concepts in service orientation. (1st December 2008) - Bubak, Oldrich; Gomaa, Hassan
Today's competitive business environment commands innovation, increasingly shorter time-to-market and efficiency. Product line technology, pioneered in manufacturing, is increasingly finding its way to the software sector allowing companies to sustain growth and achieve market success. Regardless of the domain, however, information systems have been behind all facets of business operations. Here, the emerging service oriented architectures can help provide the answers to the need for agility, versatility and economies. This effort introduces the concepts of software product lines and service orientation and explores their parallels. Next, it attempts to show the applicability of software product line methods to service orientation. Finally, the work discusses the main obstacles on the road to realising the synergy between these cutting-edge technologies.